Maternal obesity prevention: The Health in Preconception, Pregnancy, and Postpartum Early‐ and Mid‐Career Researcher Collective. (3rd February 2021) - Hill, Briony; Shrewsbury, Vanessa; Bergmeier, Heidi; Iriving, Michelle; Martin, Jane; Bailey, Cate; Walker, Ruth; Harrison, Cheryce L.; Hollis, Jenna L.; Hunter, Sue‐Anne; Kilpatrick, Michelle; Lim, Siew; et al.
Abstract : There is a clear impetus for researchers to facilitate cross‐sector and interdisciplinary collaboration to achieve collective action for maternal obesity prevention. Building early‐ and mid‐career researchers' capacity to sustainably develop collective action into the future is key. Therefore, the national Health in Preconception, Pregnancy, and Postpartum Early‐ and Mid‐career Researcher Collective (HiPPP EMR‐C) was formed. Here, we describe the aim, key goals and future directions of the HiPPP EMR‐C. Guided by the Simplified Framework for Understanding Collective Action, we aim to build our capacity as researchers, form policy stakeholder relationships and focus on generating impact to optimise maternal and child health and well‐being.